THE AUTOMATIC DOORS INTEGRATED ABSENCE AND USER ACCESS USING FINGERPRINT - Rizqia Cahyaningtiyas; Efy Yosrita; Rakhmat Arianto (Fakultas Ilmu Komputer, 2016)
This research aims to design Accompanied Door Access System Automation Absence and User Access Rights Using Integrated Fingerprint Database on Basic Computer Lab Informatics STT-PLN. What is meant by